Gongando a norma, aqüendando as Pajubeyras: ideologias linguísticas e resistência no Pajubá - Pereira, Genivan Silva (2025)
This dissertation analyzes, from a glottopolitical perspective, the Linguistic Ideologies (LIs) related to Pajubá — a linguistic repertoire originated from the contact between African languages, Brazilian Portuguese (BP) and the linguistic practices of the LGBTQIAPN+ population, especially transvestites and transsexual people — represented in lexicographic instruments such as dictionaries. The study investigates how these representations affirm or marginalize Pajubá as a linguistic and political practice permeated by power relations and symbolic disputes, having as a research problem the way in which such records reinforce, tension or subvert ideologies related to the standard norm, legitimacy and linguistic belonging in Brazil. The methodology adopted in this research is qualitative, with an exploratory, descriptive and interpretative character, according to Denzin and Lincoln (2006), based on the theoretical contributions of Kroskrity (2004), who proposes five dimensions of linguistic ideologies, and of Lagares (2018), who presents three fundamental conditions for their constitution, in addition to the studies of Araújo (2019), Barroso (2017) Del Valle (2007; 2013; 2014), Lima (2017) Melo (2016), Moita Lopes (2013). The research corpus is composed of dictionaries written in Pajubá, such as Diálogo das Bonecas (1995), Bichonário – um Dicionário gay (1996) and Aurélia – a dicionária da língua afiada (2006), whose materiality is concretized as a socio-historical and technical-cultural object, reflecting linguistic practices of resistance and identity affirmation. The analysis shows that the dictionaries Diálogo das Bonecas (1995), Bichonário (1996) and Aurélia (2006) materialize an ideological linguistic system as proposed by Lagares (2018). These works contextualize Pajubá based on the experiences of the LGBTQIAPN+ community, naturalize its terms as part of a legitimate lexicon and circulate in cultural and academic spaces, which evidences a process of institutionalization of this linguistic variety. According to Kroskrity's (2004) dimensions, Pajubá is understood as an identity marker and tool of resistance, while the dictionaries reveal the mediation of powers and the tension between marginalization and recognition. Thus, it is concluded that, when dictionaryized, Pajubá goes through ideological and power disputes, affirming itself as a discursive practice of resistance and identity of marginalized subjects. This dictionaryization not only describes the lexicon, but also produces and reproduces meanings about who has the right to speak, what can be here and which repertoires can occupy spaces of social and political visibility.